Data Mining : A Preview - Defit, Sarjon; Md. Sap, Mohd. Noor (Penerbit UTM Press, 2000)
Today's databases contain large amount of data. It is almost impossible to manually analyze valuable decision data from large databases. There are many techniques that can be used to automatically extract the knowledge from data stored in the database. One of the techniques is data mining. This paper discusses the importance of data mining, the process of knowledge discovery in database, the kind of data to be mined, the data mining task, data mining prototype and discussion about data mining today and the next future.